The city and the clock in planetary times: revisiting Isin's Being Political twenty years on. Issue 4 (4th July 2022) - McNevin, Anne
ABSTRACT: This article highlights the profound contribution to Citizenship Studies of Engin Isin's Being Political: Genealogies of Citizenship . Over the last twenty years, scholars have drawn on this seminal work to show how those positioned at the margins of citizenship have been central to its transformation. Key to Isin's approach is the notion of the city as a difference machine – a paradigmatic formulation that captures the social and spatial dimensions of citizenship struggles. Reflecting on this notion twenty years on, I ask how it intersects with an emergent planetary imaginary in which a politics of time, as much as space, is increasingly explicit. I make a case for attention to the clock, alongside and as part of the city, where the clock is understood as a non-exhaustive symbol of the temporalities in and through which subjects become political. I pursue this approach in relation to a specific example: a 2020 case before the High Court of Australia concerning the power of the Australian government to deport Aboriginal persons who were not Australian citizens. The case speaks to complex interconnections between Indigenous politics, planetary politics, and citizenship, in and through which the city and the clock are being reconfigured.